‘Malcolm X Grassroots Movement Aligns with Just and Right Struggles Everywhere in the World’ - Bakari, Akil (Prabuddha: Journal of Social Equality; Vol 1 No 1 (2018), 2018)
Interview with Akil Bakari from Malcolm X Grassroots Movement and New African People’s Organization, Mississippi, conducted by Noel Didla. This interview focuses on the organizing principles of MXGM, its philosophical guidelines, and its past and present engagements at the local, national and international levels.